Vaccine‐Associated Leptospira Antibodies in Client‐Owned Dogs. (5th March 2014) - Martin, L.E.R.; Wiggans, K.T.; Wennogle, S.A.; Curtis, K.; Chandrashekar, R.; Lappin, M.R.
<x xml:space="preserve">Abstract</x> Background Long‐term microscopic agglutination test (MAT) results after vaccination with 4‐serovar Leptospira vaccines are not available for all vaccines used in client‐owned dogs. Hypothesis/Objectives To determine antibody responses of client‐owned dogs given 1 of 4 commercially available Leptospira vaccines. Animals Healthy client‐owned dogs (n = 32) with no history of Leptospira vaccination for at least the previous year. Methods Dogs were given 1 of 4 Leptospira vaccines on week 0 and then approximately on week 3 and week 52. Sera were collected before vaccine administration on week 0 and then within 3 days of week 3, within 2 days of week 4, and approximately on weeks 7, 15, 29, 52, and 56. Antibody titers against Leptospira serovars bratislava, canicola, grippotyphosa, hardjo, icterohemorrhagiae, and pomona and were determined by MAT. Results When compared among vaccines, MAT results varied in maximal titers, the serovars inducing maximal titers, and the time required to reach maximal titers. Each vaccine induced at least some MAT titers ≥1 : 800. Most dogs were negative for antibodies against all serovars 1 year after vaccination, and anamnestic responses were variable. Conclusions and Clinical Importance Dogs vaccinated with Leptospira vaccines have variable MAT titers over time, and antibodies should not be used to predict resistance to Leptospira infection. MAT titers ≥1 : 800 can develop after Leptospira spp. vaccination, which can complicate the clinical diagnosis of leptospirosis.